Introducing role theory to analyse innovation for inclusive development systems - Kleinhans, Meraki Emmi (Stellenbosch : Stellenbosch University, 2025)
Kleinhans, M. E. 2025. Introducing role theory to analyse innovation for inclusive development systems. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/c00c8ecf-6aa5-4afd-8c5c-42fc382dedd6